1996
DOI: 10.2527/1996.74112649x
|View full text |Cite
|
Sign up to set email alerts
|

Growth, reproductive performance, mammary development, and milk production of beef heifers as influenced by prepubertal dietary energy and administration of bovine somatotropin.

Abstract: Three trials with 156 crossbred heifers were used to determine the effects of dietary energy and bovine somatotropin administration on subsequent heifer productivity. In Trial 1, heifer calves were weaned from their dams (n = 28; 113 +/- 13 d of age) and assigned to a 2 x 2 factorial arrangement of moderate (MDE) or high dietary energy (HDE) and injections of vehicle (VEH) or 250 mg of bovine somatotropin (bST) every 14 d. Heifer calves in Trial 2 (n = 28; 123 +/- 20 d of age) and Trial 3 (n = 100; 134 +/- 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
19

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 47 publications
(83 reference statements)
3
30
0
19
Order By: Relevance
“…The decreased percentage of EXT heifers being pubertal was likely the result of several factors including growth rate, winter diet, possibly monensin supplementation, which was a function of diet quality, and other behavioral and environmental factors differing in each development system. These data agree with recent literature indicating reduced postweaning ADG resulting from lower diet quality, with or without moderate realimentation before breeding, reduces the percentage of heifers attaining puberty (Granger et al, 1990;Lalman et al, 1993;Buskirk et al, 1995Buskirk et al, , 1996Marston et al, 1995;Lynch et al, 1997;Ciccioli et al, 2005;Gasser et al, 2006). Martin et al (2008) indicated reducing the percentage of mature BW at breeding by approximately 6% resulted in a nonsignificant, 17% decrease in percentage of pubertal heifers at breeding.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The decreased percentage of EXT heifers being pubertal was likely the result of several factors including growth rate, winter diet, possibly monensin supplementation, which was a function of diet quality, and other behavioral and environmental factors differing in each development system. These data agree with recent literature indicating reduced postweaning ADG resulting from lower diet quality, with or without moderate realimentation before breeding, reduces the percentage of heifers attaining puberty (Granger et al, 1990;Lalman et al, 1993;Buskirk et al, 1995Buskirk et al, , 1996Marston et al, 1995;Lynch et al, 1997;Ciccioli et al, 2005;Gasser et al, 2006). Martin et al (2008) indicated reducing the percentage of mature BW at breeding by approximately 6% resulted in a nonsignificant, 17% decrease in percentage of pubertal heifers at breeding.…”
Section: Resultssupporting
confidence: 81%
“…However, final pregnancy rate was not different (P = 0.38) between EXT and DL Nontraditional heifer development heifers. Nearly all previous research indicates postweaning BW gain restriction resulted in similar final pregnancy rates (Granger et al, 1990;Lalman et al, 1993;Buskirk et al, 1995;1996;Lynch et al, 1997;Funston and Deutscher, 2004;Ciccioli et al, 2005;Gasser et al, 2006;Martin et al, 2008). The percentage of heifers calving in the first 21 d was similar (P = 0.30; Table 7) between treatments and greater than 70% for the entire group, indicating heifers not becoming pregnant to AI became pregnant at the subsequent estrus.…”
Section: Resultsmentioning
confidence: 71%
“…But there is a lack of well founded information about this relationships independent on BW. However, BUSKIRK et al (1996) have show, that animals, get a moderate density ration eat more than such get a high density ration. Maybe, high feed intake was hold up until lactation.…”
Section: Resultsmentioning
confidence: 99%
“…Sixty pigs used in the metabolic trial were anaesthetized for the liver biopsy. Liver samples were collected and frozen in liquid nitrogen and stored at -70°C until they were analyzed for DNA and RNA contents (Sambrook et al, 1987;Buskirk et al, 1996), and protein contents using the Bradford assay (Bollag and Edelstein, 1991).…”
Section: Methodsmentioning
confidence: 99%